Bioinspired antibacterial nanostructured surfaces based on oriented calcium phosphate nanocrystals arrays against carbapenem-resistant P. aeruginosa and methicillin-resistant S. aureus - D. Squitieri; L. Degli Esposti; C. Fusacchia; M. Cacaci; R. Torelli; M. Sanguinetti; M. Iafisco; F. Bugli (Microbiologia Medica)
Not available.